Diaporthe eleutharrhenae sp. nov. Associated with a Critically Endangered Liana in China. Issue 2 (4th March 2022) - Song, Shijie; Landrein, Sven
Abstract: A new fungus isolated from the leaves of Eleutharrhena macrocarpa in southern Yunnan, China is described using morphological and molecular evidence. Phylogenetic trees based on the combined nuclear ribosomal DNA internal transcribed spacer (ITS), translation elongation factor-1α (TEF1), and β-tubulin gene (TUB2) sequences showed that Diaporthe eleutharrhenae sp. nov. is sister to Diaporthe chinensis N.I. de Silva, Lumyong & K.D. Hyde and morphologically differs in shorter alpha conidia (5–8.5 × 1.5–2 µm) and the presence of beta conidia. This study also resolves a nomenclatural problem, as two taxa were published using the same name. To avoid confusion, the unrelated D. chinensis H. Dong, J. W. Xia & X. G. Zhang is here renamed as D. dongii (H. Dong, J. W. Xia & X. G. Zhang) S. J. Song & Landrein, sp. nov. in honor of the author that described this species. Study and description of fungi associated with threatened tropical species could help to understand their ecology as well as the potential spread of fungi onto cultivated crop species.